Aplicação da termografia no infravermelho no controle da qualidade em indústrias de alimentos - Voss, Mônica (2020)
The official methods used for the determination of alcohol content of beverages require a previous stage of distillation, with limitations as low throughput and time- and energy-consuming steps. Another challenge to be overcome in the food industries is the non-invasive, non-destructive and in situ verification of the presence of food residues and bacterial biofilms on the metallic surfaces of equipment and utensils. Firstly, a new method was proposed in this work, combining paper devices and thermal infrared enthalpimetry (TIE-P) for simple, green and high-yield determination of the alcohol content of distilled beverages. The dilution heat between water and ethanol was explored and temperature changes were measured using an infrared camera. The results obtained with the TIE-P showed an agreement of 98.8 to 101.4% with the official method (AOAC), in addition to presenting a high frequency of analysis (480 samples per h), a reduction of three orders of magnitude in the consumption of energy, 560 times in the analysis time, 2000 times in the water footprint and insignificant environmental impacts compared to the AOAC method (1.9x 10-5, 7.22 kg CO2eq). Afterwards, the infrared thermography was used for the detection of residues and bacterial biofilms on the metallic surfaces. Active thermography was used and sources of heat and cold were used to generate a thermal gradient between stainless steel and residue and/or biofilm. The presence of Pseudomonas aeruginosa biofilms on stainless steel coupons was evaluated and the images with those from scanning electron microscope (SEM). A free software (Thermofilm) was developed for image processing and the results compared to ImageJ. A good agreement (87.7 to 103.8%) was obtained in relation to ImageJ and images of coupons treated with disinfectant (peracetic acid) were obtained to show the applicability of the proposed method for biofilm studies. All analytical steps can be performed in 3 minutes, being non-invasive, non-destructive, low-cost, portable and easy to use. Lastly, active thermography was used for the detection of residues on the knives used in meat industry. The temperature of -11 °C and 5 s for reading were suitable for the detection of food residues simulated contamination. The intermediate precision and repeatability of the proposed method showed relative standard deviations <7% and good accuracy (from 86 to 103%). Therefore, this result showed that the proposed method can be applied in routine analyzes for the detection of food residues on knife blades. Therefore, the proposed infrared thermographic methods in this work presented excellent performance, being an adequate alternative for application in routine analysis, due to the low cost, high frequency of analysis and simplicity.